PENGARUH PERILAKU KEWIRAUSAHAAN GENERASI MUDA DI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN DILIHAT DARI THEORY OF PLANNED BEHAVIOR - Dini, Dini; Fahmi Oemar; Fatkhurahman, Fatkhurahman (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2025)
This study aims to determine the influence of attitudes, subjective norms and perception of behavior control on the entrepreneurial behavior of the younger generation in Pangkalan Kuras District, Pelalawan Regency with entrepreneurial intentions as an intervention. This study uses this research using a quantitative method and the PLS Structural equational modelling (SEM) statistical test will be used for verifiable analysis. The research was conducted in Pangkalan Kuras District, Pelalawan Regency with a total of 93 respondents. The results of the study show that entrepreneurial intention as an intervening variable has a positive value on the influence of Attitude Variables, Subjective Norms and Behavioral Control on Entrepreneurial Behavior Variables of the young generation in Pangkalan Kuras District, Pelalawan Regency. This means that the entrepreneurial intention variable as an intervening will strengthen the relationship between Attitude Variables, Subjective Norms and Behavioral Control to the Entrepreneurial Behavior Variables of the young generation in Pangkalan Kuras District, Pelalawan Regency, because indeed with a strong entrepreneurial intention, the young generation will focus their attention and will do something to their entrepreneurship so as to give rise to a business that runs in an organized and orderly manner and be able to see business opportunities with the right risk-taking. To foster an entrepreneurial attitude among young people in the Pangkalan Kuras District area is very important in creating a generation that not only appears in work, but is also able to create a generation that is able to create jobs and contribute to the economy. For this reason, in order for the attitude of the young generation in Pangkalan Kuras District to remain consistent in running the business that has been pursued so far, these young entrepreneurs must have a courageous attitude in taking risks and speed of decision-making to seize existing opportunities so that they can improve their business performance